New syllabus Oxford primary Mathematics workbook 2B - Yee, Dr Foong Pui (Karachi : Oxford university press, 2019)
The Oxford New Syllabus Primary Mathematics Workbook 2B is a companion workbook for Oxford New Syllabus Primary Mathematics Book 2, designed for second-year primary school students. This workbook provides additional exercises and practice to reinforce the mathematical concepts taught in the main textbook, with an emphasis on developing problem-solving skills and mathematical fluency.
Keywords: Mathematics : Textbook